Object Motion Manipulation and time perception in virtual reality - Landeck, Maximilian; Unruh, Fabian; Lugrin, Jean-Luc; Latoschik, Marc Erich (Frontiers in Virtual Reality, 2024)
This paper presents a novel approach to altering how time is perceived in Virtual Reality (VR).It involves manipulating the speed and pattern of motion in objects associated with timekeeping, both directly (such as clocks) and indirectly (like pendulums). Objects influencing our perception of time are called 'zeitgebers'; for instance, observing a clock or pendulum tends to affect how we perceive the passage of time. The speed of motion of their internal parts (clock hands or pendulum rings) is explicitly or implicitly related to the perception of time. However, the perceptual effects of accelerating or decelerating the speed of a virtual clock or pendulum in VR is still an open question. We hypothesize that the acceleration of their internal motion will accelerate the passage of time and that the irregularity of the orbit pendulum's motion will amplify this effect. We anticipate that the irregular movements of the pendulum will lower boredom and heighten attention, thereby making time seem to pass more quickly. Therefore, we conducted an experiment with 32 participants, exposing them to two types of virtual zeitgebers exhibiting both regular and irregular motions. These were a virtual clock and an orbit pendulum, each operating at slow, normal, and fast speeds. Our results revealed that time passed by faster when participants observed virtual zeitgebers in the fast speed condition than in the slow speed condition. The orbit pendulum significantly accelerated the perceived passage of time compared to the clock. We believe that the irregular motion requires a higher degree of attention, which is confirmed by the significantly longer gaze fixations of the participants. These findings are crucial for time perception manipulation in VR, offering potential for innovative treatments for conditions like depression and improving well-being. Yet, further clinical research is needed to confirm these applications.